Malaysian Chinese speakers' attitudes towards Foochow, Hokkien and Mandarin - Puah, Yan Yann; Ting, Su Hie (Routledge, 2015)
The study examines the influence of gender, age and socio-economic status on attitudes of Foochow and Hokkien towards their ethnic language and Mandarin. The matched guise test results of 120 Foochow and 120 Hokkien participants in Kuching, Malaysia, showed positive attitudes towards Mandarin on all the 15 traits. The Hokkien participants were more positive than the Foochow participants towards speakers of their own ethnic language. Foochow speakers were perceived as loud, and the male Foochow speaker was rated unfavourably on five other traits. Multivariate analysis of variance results showed that gender significantly influenced the Foochow participants' ratings of the wealth of Foochow speakers and the Hokkien participants' ratings of the easy-going nature of Mandarin speakers, the gentleness and solidarity of the male Mandarin speaker, and the height and intelligence of the male Hokkien speaker. Age influenced the attributions of status to the female Foochow speaker and solidarity with the female Mandarin speaker. Socio-economic status influenced the ratings of the most number of traits. Interaction effects were also found. The underlying dimensions loaded onto one factor each for Foochow (easy-going and rich) and Hokkien (formal, strong solidarity) and two different factors for Mandarin, suggesting different stereotypes of dialect and Mandarin speakers.